A Study of the Opinions on Buying Health Insurance using Ridit Analysis - Sittimongkol, Roumporn; Hashim, Suramase (PKRU SciTech Journal, 2022)
This research aimed to study and compare the market mix strategy: product price place and promotion which related to the opinions on buying health insurance using Ridit and mean analyses. Because the opinions on purchasing health insurance are expressed on a Likert scale, which is an ordinal scale, Ridit analysis is appropriate for analyzing these data. The Ridit analysis is used in this study to rank and compare opinions on the market mix strategy about buying health insurance. The results indicated that the opinion on the appropriate and fair price of insurance premiums had the highest impact on the purchase of health insurance. The second most impact in purchasing was about the opinions related to product, which are reliable of the company, clear and understandable form of health insurance, and the insurance policy that matches the demands. By applying the Ridit analysis to the study of opinions on buying health insurance in this study, it was possible to summarize and prioritize opinions about health insurance purchases as a guide for future creating marketing strategies.